Ag-rGO content dependence of the mechanical, conductive and anti-corrosion properties of copper matrix composites. (17th August 2018) - He, Yezeng; Wang, Shitong; Luo, Haibo; Wang, Cong
Abstract: Using silver-modified reduced graphene oxide (Ag-rGO) as reinforcement, we fabricated copper matrix composites through vacuum uniaxial hot-pressing sintering method. The results clearly show that the properties of the Ag-RGO/Cu are closely related to the Ag-RGO content. The composite containing 2.4 vol% Ag-RGO has the highest tensile strength and microhardness, 60% and 42% higher than that of pure Cu, respectively. The Tafel analysis indicates that the composites with 1.6 vol% Ag-RGO has the best corrosion resistance. Additionally, the electronic and thermal conductivity is found to decrease with increasing the Ag-RGO content. This work is expected to provide a strategy to prepare novel copper materials with unique properties.